Two new species of Cololejeunea (Spruce) Schiffn. from Western Ghats, India. (3rd April 2019) - Asthana, Geeta; Srivastava, Abha
ABSTRACT: Introduction. During a recent floristic survey of liverworts from Western Ghats, India, two interesting liverworts of genus Cololejeunea were collected from forests in Mahabaleshwar in the state of Maharashtra. Methods. After critical investigation, they have been described as new to science and both species, C. ghatensis G.Asthana & A.Srivastava sp. nov. and C. mehrana G.Asthana & A.Srivastava sp. nov. are illustrated and described here. Key results. Cololejeunea ghatensis is an epiphyllous species growing on angiosperm leaves and has been collected near Chinaman Waterfall, Robbers Cave, Connaught Peak and Polo Ground area. Cololejeunea mehrana has been collected near Monkey point and the latter has an interesting habitat as it was found growing on moss leaves. Cololejeunea ghatensis is monoicous and C. mehrana is dioicous.